A Detailed Decomposition Analysis of the Public-Private Sector Wage Gap in South Africa - Prudence Kwenda; Miracle Benhura (Institute for the Study of Labor (IZA), 2015)
The present study examines the public-private sector wage gap in South Africa using individual cross section data for 2000-7. Results from unconditional quantile regressions and generalised Oaxaca-Blinder type decompositions show that the wage gap is inverted-U shaped across the wage distribution. The 'composition' effect is more important than the 'price' effect at the bottom of the distribution while the opposite applies at the top. Key factors underpinning the 'composition' effect are unionisation, industry of employment and education, while those associated with the 'price' effect are education, race and occupation.
Keywords: C21; J31; J45; 330; public sector; wage gap; recentered influence function; decomposition